2014
DOI: 10.1097/won.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Unavoidable Pressure Injury

Abstract: In the vast majority of cases, appropriate identification and mitigation of risk factors can prevent or minimize pressure ulcer (PU) formation. However, some PUs are unavoidable. Based on the importance of this topic and the lack of literature focused on PU unavoidability, the National Pressure Ulcer Advisory Panel hosted a multidisciplinary conference in 2014 to explore the issue of PU unavoidability within an organ system framework, which considered the complexities of nonmodifiable intrinsic and extrinsic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(67 citation statements)
references
References 166 publications
1
63
0
3
Order By: Relevance
“…The fact that patients with malnutrition and multiple comorbidities were at increased risk for developing a pressure ulcer was asserted in 2014 National Pressure Ulcer Consensus Conference. [ 20 21 ] New onset weight loss has been identified as a risk factor for mortality in elderly patients. [ 22 ] Two studies on individuals in long-term care facilities showed that a 5% decrease in body weight occurring over 30 days was associated with a higher mortality risk.…”
Section: R Esearch a Bout N mentioning
confidence: 99%
“…The fact that patients with malnutrition and multiple comorbidities were at increased risk for developing a pressure ulcer was asserted in 2014 National Pressure Ulcer Consensus Conference. [ 20 21 ] New onset weight loss has been identified as a risk factor for mortality in elderly patients. [ 22 ] Two studies on individuals in long-term care facilities showed that a 5% decrease in body weight occurring over 30 days was associated with a higher mortality risk.…”
Section: R Esearch a Bout N mentioning
confidence: 99%
“…HAPU are considered preventable events and Medicare applies payment penalties to the bottom 25% lowest performing hospitals—a measure that was implemented in 2015 [ 16 , 17 ]. However, based on a consensus statement by the Wound Ostomy and Continence Nurses Society “unavoidable pressure ulcers do occur” [ 18 ] (p. 328).…”
Section: Introductionmentioning
confidence: 99%
“…1–3 PrUs, which are largely preventable, 4,5 are painful and debilitating, reduce quality of life, and can lead to septic infections and premature death. 3,6 Additional adverse consequences of PrUs in the US include high treatment costs (~ $20,900 to $151,700 per patient), and litigation.…”
mentioning
confidence: 99%